Pengaruh Teknik Extinction terhadap Prokrastinasi Akademik Remaja di Korong Matua Nagari Sikucua Timur Kabupaten Padang Pariaman - Adidiningrum, Retno; Santosa, Budi (MASALIQ, 2023)
This research was carried out based on the phenomenon that existed in Korong Matua Nagari Sikucua Timur, Padang Pariaman Regency which showed that there were teenagers in this Korong who were less responsible for their learning activities, were less able to choose their own learning activities and there were also teenagers who lacked initiative and lacked able to do the task independently. To increase the change in adolescent academic procrastination, one of the services provided in counseling guidance is implemented, namely group counseling. The goal to be achieved in this research is to find out whether there is a significant difference before and after the extinction technique is given to academic procrastination. This research belongs to the pre-experimental model of One Group Pretest Posttest Design. The population is all adolescents in Korong Matua at the junior and senior high school levels, 20 people, while the technique used in sampling is the Non-Random Sampling technique, namely Purposive Sampling where sampling is based on certain considerations, the sample in this study is 10 junior high and high school level youth person. The data collection instrument is a Likert scale. Data on adolescent learning independence was collected through a scale, then analyzed using the Wilcoxon Rank Test with the help of SPSS 22. The results of the research that are known from the results of the Z test (Wilcoxon) show the difference between pretest and posttest scores. From the results of the calculation of the Wilcoxon test, a significant p value of -2,805 was obtained. Based on the applicable provisions, it is known that the results of the Wilcoxon sig p-value test are 0.004 <α(α = 0.05), which means that Ha is accepted and Ho is rejected. This means that there is a change in Adolescent Academic Procrastination before and after being given the Extinction technique.